THE EFFECT OF PICTIONARY GAME TOWARDS STUDENTS’ VOCABULARY MASTERY AT THE EIGHTH GRADE STUDENTS OF MTs NURUL HIDAYAH MALINGPING LEBAK BANTEN IN ACADEMIC YEAR 2023/2024 - Indah Kusuma Nengsih; Riandi; Rizdki Elang Gumelar (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2023)
This research aimed to investigated the significant effect of Pictionary Gametoward the students’ vocabulary mastery. This research approach was quantitative approach and a quasi-experimental method with achievement test in collecting data. Achievement test included pr-test and post test. The population was 40 students and the sample of this research was 40 students that consisted of 20 student of experimental class and 20 student of control class. The experimental class used Pictionary Game and control class used Mime Game. The data was analyzed by using statistical of program SPSS22. Based on the result of data analysis, the result showed that mean of post-test both experimental and control class different are 69.35 and 58.20 and for the result of t-test obtained sign score 0.000 <a = 0.05. The result indicated the alternative hypothesis was accepted and the null hypothesis was rejected. Based on the findings of this research, there is significant PictionaryGametowards students’vocabulary mastery.